2018
DOI: 10.1111/1365-2664.13265
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic wide‐ranging movements lead to upwardly biased occupancy in a territorial species

Abstract: 1. Occupancy modelling is useful for inferring population status and dynamics when occupancy reflects the presence of established individuals or populations, such as residents detected at breeding sites. However, if occupancy is assumed to reflect the presence of established residents but reflects transient movements from nonresidents at truly unoccupied sites, inferences about population status will be overly optimistic. In population monitoring, detections arising from dispersing or wide-ranging individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
(82 reference statements)
1
37
0
Order By: Relevance
“…It has been shown that even low rates of false positive detections result in positive biases that inflate occupancy rate estimates (Royle and Link 2006, Miller et al 2011, Sutherland et al 2013. We also knew from GPS-tagbased studies of spotted owls that owls frequently move amongst unoccupied (and sometimes occupied) territories (Berigan et al 2018, Blakey et al 2019). Therefore, we were able to exclude false positive detections from our owl detection database because we knew which owls were present at a given historical territory owing to our observation of their colour bands, both before and after the King Fire.…”
Section: The Science Of Spotted Owls and Firementioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that even low rates of false positive detections result in positive biases that inflate occupancy rate estimates (Royle and Link 2006, Miller et al 2011, Sutherland et al 2013. We also knew from GPS-tagbased studies of spotted owls that owls frequently move amongst unoccupied (and sometimes occupied) territories (Berigan et al 2018, Blakey et al 2019). Therefore, we were able to exclude false positive detections from our owl detection database because we knew which owls were present at a given historical territory owing to our observation of their colour bands, both before and after the King Fire.…”
Section: The Science Of Spotted Owls and Firementioning
confidence: 99%
“…We had an extensive individual history of owls affected by the King Fire because we had colour-marked and resighted birds in our study area for the 22 years preceding (1993-2014) as well as annually after the King Fire. Knowing the identity of individuals allowed us to associate individuals with places and, more importantly, allowed us to exclude false positive detections in survey/location histories of birds (Berigan et al 2018). Interestingly, studies by Lee et al (2012Lee et al ( , 2013, Lee and Bond (2015) and Hanson et al (2018) on occupancy dynamics of spotted owls showed no negative effects of high-severity fire but relied primarily on night-time detections of unmarked owls to assign the occupancy status, which suggests false positive detections could have been included in analysis (Berigan et al 2018).…”
Section: The Science Of Spotted Owls and Firementioning
confidence: 99%
See 2 more Smart Citations
“…For example, spotted owls typically show high site fidelity (Forsman et al 2002;Blakesley et al 2006;Ganey et al 2014b), and resident owls may therefore continue to occupy territories immediately following fire even if the habitat within those territories is severely degraded (Ganey et al 2017). More importantly, recent data on movements of Global Positioning System-tagged California spotted owls suggest that, at least for that subspecies, occupancy rates estimated based on locations of unmarked owls may badly overestimate true occupancy rates (Berigan et al 2018;Blakey et al 2019). Further, in a long-term study involving uniquely marked northern spotted owls, Rockweit et al (2017) found that occupancy rates in severely burned territories remained relatively high over time, but survival rates in these territories were lower and turnover rates were higher than in unburned or lightly burned territories.…”
Section: Pre-and Post-fire Predicted Nesting Habitat Suitabilitymentioning
confidence: 99%